Effects of naloxone on upper airway collapsibility in normal sleeping subjects. Issue 8 (August 1996) - Meurice, J. C.; Marc, I.; Sériès, F.
Abstract : BACKGROUND: To evaluate the possible influence of endorphin release on upper airway collapsibility the effects of naloxone, an opiate receptor antagonist, were measured. METHODS: The effects of naloxone on upper airway collapsibility were studied in five normal sleeping men in a pilot study. During a sleep fragmentation night the subjects received either naloxone or a volume matched saline placebo in a double blind crossover design. Critical pressure (Pcrit) was measured during a morning nap following sleep fragmentation. RESULTS: The plasma levels of endorphins increased during sleep fragmentation nights. Pcrit was significantly greater after placebo than after naloxone infusion. CONCLUSIONS: Naloxone may reduce upper airway collapsibility in normal sleeping subjects following sleep fragmentation.